Murder in Passy - Black, Cara, 1951- (Black, Cara, 1951- Aimée Leduc investigation., 2011)
When Aimee Leduc's godfather, Morbier, a police "commissaire," asks her to check on his girlfriend at her home there, Aimee finds Xavierre, a "haut bourgeois" matron of Basque origin, strangled in her garden while Aimee waits inside. Circumstantial evidence makes Morbier the prime suspect, and to vindicate him, Aimee must identify the real killer.